Assessment of Effectiveness of E-Learning Tablet (OPON-IMO): A Package for Teaching-Learning in Senior Secondary Schools in Osun State - O., Adeniyi, W. (American Journal of Education and Learning, 2019)
For any meaningful teaching-learning to take place in schools, it is important that students are well directed, guided, facilitated, and supported with device that will enhance attainment of academic goals. Hence, the thrust of the study was to investigate the acceptability and the knowledge of students on the use of tablet as well as ascertaining the influence these have on the effective teaching-learning and academic performance of students. The sample of 250 senior secondary school teachers were selected from 12 schools in Osun State using multistage sampling technique. The results showed that 106(42.4%) of the teachers moderately perceived that their students accepted the e-learning tablet for teaching-learning activities. It showed that 127(50.8%) of the teachers indicated that their students possessed average knowledge on how to use e-learning tablet for learning. Also, the result showed that the most perception among the teachers was that textbook materials in the tablet were relevant and appropriate ( = 2.9840, S.D = 0.87338). Again, the result revealed a significant influence of levels of acceptability of e-learning tablet on teaching-learning activities in senior secondary schools (F = 23.865, p < 0.05). Finally, the result showed a significant influence of students’ knowledge on use of e-learning tablet on their academic performance (F= 58.472, p < 0.05). The study concluded that most teachers perceived that their students welcomed the integration of the e-learning tablet into teaching-learning and that the learning materials in the tablet were relevant and appropriate.